Antimicrobial Polymers: Mimicking Amino Acid Functionali ty, Sequence Control and Three-dimensional Structure of Host-defen se Peptides - Hartlieb, Matthias; Williams, Elizabeth G. L.; Kuroki, Agnès; Perrier, Sébastien; Locock, Katherine E. S. (Current Medicinal Chemistry, 2017)
Peptides and proteins control and direct all aspects of cellular function and communication. Having been honed by nature for millions of years, they also typically display an unsurpassed specificity for their biological targets. This underlies the continued focus on peptides as promising drug candidates. However, the development of peptides into viable drugs is hampered by their lack of chemical and pharmacokinetic stability and the cost of large scale production. One method to overcome such hindrances is to develop polymer systems that are able to retain the important structural features of these biologically active peptides, while being cheaper and easier to produce and manipulate chemically. This review illustrates these principles using examples of polymers designed to mimic antimicrobial host-defence peptides. The host-defence peptides have been identified as some of the most important leads for the next generation of antibiotics as they typically exhibit broad spectrum antimicrobial ability, low toxicity toward human cells and little susceptibility to currently known mechanisms of bacterial resistance. Their movement from the bench to clinic is yet to be realised, however, due to the limitations of these peptides as drugs. The literature provides a number of examples of polymers that have been able to mimic these peptides through all levels of structure, starting from specific amino acid sidechains, through to more global features such as overall charge, molecular weight and threedimensional structure (e.g. α-helical). The resulting optimised polymers are able retain the activity profile of the peptides, but within a synthetic macromolecular construct that may be better suited to the development of a new generation of antimicrobial therapeutics. Such work has not only produced important new leads to combat the growing threat of antibiotic resistance, but may also open up new ways for polymers to mimic other important classes of biologically active peptides.
Keywords: peptide mimic